1998
DOI: 10.1590/s0034-89101998000600010
|View full text |Cite
|
Sign up to set email alerts
|

Infecção por Trypanosoma cruzi em candidatos a doador de sangue

Abstract: BONAMETTI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
5
0
2
Order By: Relevance
“…The results showed that the use of two or more different tests by blood banks prevents transfusion associated Chagas disease. Trypanosoma cruzi infection in blood donors Bonamett et al 15 1998 Revista de Saúde Pública Descriptive quantitative study: retrospective. To evaluate seropositivity for T. cruzi infection in blood donors and to compare this rate with those found in blood Banks in 1958 and 1975.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the use of two or more different tests by blood banks prevents transfusion associated Chagas disease. Trypanosoma cruzi infection in blood donors Bonamett et al 15 1998 Revista de Saúde Pública Descriptive quantitative study: retrospective. To evaluate seropositivity for T. cruzi infection in blood donors and to compare this rate with those found in blood Banks in 1958 and 1975.…”
Section: Resultsmentioning
confidence: 99%
“…The countries with the highest prevalence of T. cruzi 3 . The manifestation of the chronic disease has a considerable geographic variation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, according to the Coordination of Blood and Hemoderivates of the Ministry of Health this figure for the state as whole had decreased to 0.86% in 1995 6 . In the city of Londrina, data collection carried out by various authors in the years of 1958, 1975, 1996 and 1998, found a decreasing seroprevalence of 6.92%, 7.49%, 1.4% and 1.3%, respectively 4,5,31,32 . Nowadays, with the main way of transmission under control, the principal concern is regarding assistance to infected individuals, particularly their situation in the job market, the social services involved and the necessity for adequate medical care 18 .…”
Section: Introductionmentioning
confidence: 99%